Establishing breast feeding in infants with Down syndrome: the FADES cohort experience. Issue 1 (10th November 2022) - Williams, Georgina M; Leary, Sam; Leadbetter, Sofia; Toms, Stu; Mortimer, Georgina; Scorrer, Tim; Gillespie, Kathleen; Shield, Julian P H
Abstract : Objective: To describe breastfeeding prevalence and maternal experience in infants with trisomy 21. Design: Longitudinal cohort study. Setting: Participants from UK recruited through websites, social media and local collaborators: neonatologists, community paediatricians and research nurses. Subjects: Infants under the age of 8 months with Down syndrome (DS) recruited to the Feeding and Autoimmunity in Down Syndrome Evaluation Study between 1 September 2014 and 31 August 2017. Seventy participants: median age 20 weeks (IQR 13–29 weeks) at initial questionnaire. Main outcome measure: Breastfeeding prevalence at 6 weeks and 6 months among infants with DS. Results: The prevalence of exclusive breast feeding among study participants was similar to the general population (13/61, 21% vs 23% at 6 weeks, 2/54, 4% vs 1% at 6 months). However, the prevalence of breast feeding (exclusive or combination feeding) among the study participants was higher than the general population (39/61 64% vs 55% at 6 weeks, 32/59 54% vs 34% at 6 months). Conclusion: Although there may be challenges in establishing breast feeding in infants with DS, our data suggest that exclusive breast feeding is possible for some, and the prevalence of breast feeding is comparable to the prevalence in the general population. Trial registration number: ISRCTN12415856